Study of the characteristics of mineral suspensions for the development of equipment for the separation of finely dispersed rock mass - Nadutiy, V. P.; Chelyshkina, V. V.; Kurilov, V. S. (Журфонд, 2020)
Calculation of hydraulic devices and apparatuses for extracting valuable components from mineral suspensions is based on determining the speed of the constrained motion of particles. For calculation of the speed, it is necessary to know the characteristics of the suspension - viscosity, porosity, density. A method for analytical calculation of these characteristics has been developed. Its peculiarity is that all characteristics are related only to the bulk density of the medium, which is easily determined in practice by weighing. The results of analytical calculations of the characteristics are given using the example of two suspensions - with a solid particle density of 2.65 g/cm 3 (amber sands) and 2.0 g/cm 3 (crushed tuff) with a medium density of up to 1.8 g/cm 3 . The described method can also be used for multicomponent mixtures. It allows to predict the change in the characteristics of the slurry from the operating parameters of the equipment. The method is used to assess technological modes and determine structural indicators in the design of hydraulic devices and apparatuses.

Розрахунок гідравлічних пристроїв і апаратів для вилучення цінних компонентів з мінеральних суспензій заснований на визначенні швидкості туго руху частинок. Для розрахунку швидкості потрібно знати характеристики суспензії - в'язкість, поростісь, щільність. Розроблено метод аналітичного розрахунку зазначених показників. Його особливістю є те, що всі характеристики пов'язані лише з об'ємною щільністю середовища, яка легко визначається на практиці методом зважування. Наведено результати аналітичних розрахунків характеристик на прикладі двох суспензій – з щільністю твердих частинок 2,65 г/см 3 (янтароносні піски) і 2,0 г/см 3 (подрібнений туф) при щільності середовища до 1,8 г/см 3 . Викладений метод також можна використовувати для багатокомпонентних сумішей. Він дозволяє прогнозувати зміну характеристик пульпи від режимних параметрів обладнання. Метод використовується для оцінки технологічних режимів і визначення конструкторських показників при проектуванні гідравлічних пристроїв і апаратів.
Дослідження характеристик мінеральних суспензій для розробки обладнання для поділу тонкодисперсної гірської маси
Keywords: мінеральна суспензія; в'язкість; пористість; щільність; mineral suspension; viscosity; porosity; density